Contribution of Puma to Inflammatory Resolution During Early Pneumococcal Pneumonia - Kennedy II, Daniel E.; Mody, Perceus; Gout, Jean-Francois; Tan, Wei; Seo, Keun Seok; Olivier, Alicia K.; Rosch, Jason W.; Thornton, Justin A. (Frontiers in Cellular and Infection Microbiology, 2022)
Apoptosis of cells at the site of infection is a requirement for shutdown of inflammatory signaling, avoiding tissue damage, and preventing progression of sepsis. Puma+/+ and Puma-/- mice were challenged with TIGR4 strain pneumococcus and cytokines were quantitated from lungs and blood using a magnetic bead panel analysis. Puma-/- mice exhibited higher lung and blood cytokine levels of several major inflammatory cytokines, including IL-6, G-CSF, RANTES, IL-12, IFN-ϒ, and IP-10. Puma-/- mice were more susceptible to bacterial dissemination and exhibited more weight loss than their wild-type counterparts. RNA sequencing analysis of whole pulmonary tissue revealed Puma-dependent regulation of Nrxn2, Adam19, and Eln. Enrichment of gene ontology groups differentially expressed in Puma-/- tissues were strongly correlated to IFN-β and -ϒ signaling. Here, we demonstrate for the first time the role of Puma in prohibition of the cytokine storm during bacterial pneumonia. These findings further suggest a role for targeting immunomodulation of IFN signaling during pulmonary inflammation. Additionally, our findings suggest previously undemonstrated roles for genes encoding regulatory and binding proteins during the early phase of the innate immune response of pneumococcal pneumonia.